Optimizing UNU/ICTP PFF Plasma Focus for Neon Soft X-ray Operation - Saw, S. H.; Lee, P. C. K.; Rawat, Rajdeep Singh; Lee, Sing (IEEE, 2009)
The United Nations University/International Centre for Theoretical Physics Plasma Focus Facility (UNU/ICTP PFF), a 3.3-kJ plasma focus, was designed for operation in deuterium with a speed factor S such that the axial run-down time matches the current rise time at an end axial speed of nearly 10 cm/μs. For operation in neon, we first consider that a focus pinch temperature between 200 and 500 eV may be suitable for a good yield of neon soft X-rays, which corresponds to an end axial speed of 6–7 cm/μs. On this basis, for operation in neon, the standard UNU/ICTP PFF needs to have its anode length z0 reduced by some 30%–40% to maintain the time matching. Numerical experiments using the Lee model code are carried out to determine the optimum configuration of the electrodes for the UNU/ICTP PFF capacitor system. The results show that an even more drastic shortening of anode length z0 is required, from the original 16 to 7 cm, at the same time, increasing the anode radius “a” from 0.95 to 1.2 cm, to obtain an optimum yield of Ysxr = 9.5 J. This represents a two- to threefold increase in the Ysxr from that computed for the standard UNU/ICTP PFF.